The Use of the Neoglycolipid-Based Oligosaccharide Microarray System in the Diagnosis of Endometriosis – Preliminary Study - Wojtyla C; Tołwiński I; Laudański P (Dove Medical Press, 2024)
Cezary Wojtyla,1,2 Ignacy Tołwiński,3 Piotr Laudański1,2,4 1Women's Health Research Institute, Calisia University, Kalisz, Poland; 2OVIklinika Infertility Center, Warsaw, Poland; 3Warsaw Southern Hospital, Warsaw, Poland; 4Department of Obstetrics, Gynecology and Gynecological Oncology, Medical University of Warsaw, Warsaw, PolandCorrespondence: Cezary Wojtyla, Women's Health Research Institute, Calisia University, Kalisz, Poland, Email c.wojtyla@uniwersytetkaliski.edu.plObjective: Endometriosis presents diagnostic challenges, and there is a need for developing novel biomarkers with satisfactory specificity and sensitivity. Glycomics, exploring glycosylation changes in glycoproteins, offers potential solutions. The aim of this study was to analyze the carbohydrate-binding properties of IgG and IgM antibodies in the plasma and peritoneal fluid samples and to identify any differences in the presence and the specificities of anti-carbohydrate antibodies in the endometriosis patient and the controls.Methods: Multicenter study was conducted in Poland between 2018 and 2019. Plasma and peritoneal fluid samples were collected from women undergoing laparoscopic surgery. Endometriosis patients (n=8) and controls (n=8), matched for cycle phase and disease stage, were selected. The neoglycolipid-based oligosaccharide microarray system was used to investigate IgG and IgM antibody binding properties to glycan-related probes in biological materials.Results: In peritoneal fluid samples, IgM binding to the following probes was significantly higher in endometriosis: GSC-915-4 (new), LNFP-I, NeuAcα-(6')LNnO (F1), B-like decaosylceramide, log10(GM1-penta), and log10(GSC-915-5). In a control group higher IgG binding to log10(Orsay-5-AO) was observed. In plasma samples, endometriosis showed higher IgG binding to log10(NeuAcα-(6')LNnO (F1)) and lower IgG binding to Gal2GlcNAc(1-3)-AO. After Benjamin-Hochberg correction, differences were not significant. Effect sizes highlighted some glycan probes in both plasma and peritoneal fluid. Strong correlations were observed among binding to certain glycan probes.Conclusion: This preliminary study suggests glycomics' potential contribution to endometriosis diagnosis and understanding of its pathophysiology. Neoglycolipid-based microarrays hold promise for non-invasive endometriosis diagnostic tools. Further investigations with larger cohorts are warranted to validate these findings and explore potential correlations with antibody levels in plasma and peritoneal fluid. Glycomics emerges as a valuable diagnostic asset in endometriosis research.Keywords: endometriosis, glycomics, diagnosis, microarray